Patterns of spontaneous recovery of neglect and associated disorders in acute right brain-damaged patients. Issue 10 (16th September 2004) - Farnè, A; Buxbaum, L J; Ferraro, M; Frassinetti, F; Whyte, J; Veramonti, T; Angeli, V; Coslett, H B; Làdavas, E
Abstract : Objectives: The evolutionary pattern of spontaneous recovery from acute neglect was studied by assessing cognitive deficits and motor impairments. Detailed lesion reconstruction was also performed to correlate the presence of and recovery from neglect to neural substrates. Methods: A consecutive series of right brain-damaged (RBD) patients with and without neglect underwent weekly tests in the acute phase of the illness. The battery assessed neglect deficits, neglect-related deficits, and motor impairment. Age-matched normal subjects were also investigated to ascertain the presence of non lateralised attentional deficits. Some neglect patients were also available for later investigation during the chronic phase of their illness. Results: Partial recovery of neglect deficits was observed at the end of the acute period and during the chronic phase. Spatial attention was impaired in acute neglect patients, while non spatial attentional deficits were present in RBD patients with and without acute neglect. A strong association was found between acute neglect and fronto-parietal lesions. Similar lesions were associated with neglect persistence. In the chronic stage, neglect recovery was paralleled by improved motor control of the contralesional upper limb, thus emphasising that neglect is a negative prognostic factor in motor functional recovery. Conclusions: These findings show that spatial attention deficits partially improve during the acute phase of the disease in less than half the patients investigated. There was an improvement in left visuospatial neglect at a later, chronic stage of the disease, but this recovery was not complete.